Classification and evaluation of crop storage structures in Western Nigeria (1993)
A survey involving the use of questionnaires and personal communication during field trips was carried out in Western Nigeria with the aim of classifying and assessing the efficiency of the existing structures for the storage of crops. Barns; cribs; trenches; platforms; warehouses and silos are among the important Storage structures. The existing structures could be efficient with proper management but a major limitation of most of them is the low unit capacity which is inadequate to cope with the present volume of agricultural production. Research efforts should concentrate more on improving the existing structures rather than their replacement.